Acropora tenuis energy acquisition along a natural turbidity gradient - Zweifler, A.; Browne, Nicola; Levy, O.; Hovey, R.; O’Leary, M. (2024)
Predicted future increases in both local and global stressors are expected to lead to elevated turbidity levels and an expansion of the geographical range of turbid coral reefs. Corals typically respond to elevated turbidity by increasing their rates of heterotrophy as means of compensating for low energy levels from reduced light and photosynthesis. We analysed Acropora tenuis energy acquisition along a natural turbidity gradient over two time points in Exmouth Gulf, Western Australia, using in-situ environmental data with coral physiology attributes and stable isotopes to assess trophic strategy. Our hypothesis was that as turbidity levels increased, so too would heterotrophy rates. Both δ13C and δ15N values decreased from the clear-water to the turbid sites, which along with Bayesian analysis revealed that all A. tenuis communities along the turbidity gradient are on a mixotrophic-heterotrophic feeding strategy scale. We propose that the low δ15N levels at the most turbid site may result from a combination of Acropora physiological limitations (e.g., reduced feeding capacity) and highly variable turbidity levels. In contrast, the higher δ15N at the clear-water site likely results from increased nutrient availability from additional sources such as upwelling. Our findings suggest that increased heterotrophy by coral hosts in turbid coral reef areas is not a universal pattern. Importantly, the loss of carbon in the turbid sites is not supplemented by nitrogen intake, which might suggest that Exmouth Gulfs Acropora communities are more vulnerable to future climate stressors and bleaching.